Clitic impersonal constructions in Romance: syntactic features and semantic interpretation - Mendikoetxea, Amaya (Transactions of the Philological Society, 2008)
This paper provides an overview of the syntax and semantics of Romance clitic impersonal constructions (CL-ICs), as present in the grammars of Spanish and Italian, within the framework of the Minimalist Program. Syntactically, these structures are characterised by the presence of the clitic se/si, which is analysed as a 0-person clitic, along with other person clitics in Romance, and heads a functional projection in the temporal domain immediately above T(ense). The syntactic properties of CL-ICs can be accounted for with reference to the complex agreement operations involving the clitic se/si, the empty category in subject position (a null generic pronoun: G-pro), the object argument in transitive contexts, and the features of the heads T and v. The interpretation of CL-ICs crucially relies on the presence of G-pro in the specifier position of vP: it introduces a variable that can be bound by an existential or a universal quantifier, which accounts for the variable quantificational force of CL-ICs. Adapted from the source document